Cases Where Soft Power is Being Ignored - Luli, Elira (European Journal of Multidisciplinary Studies, 2016)
Today, in times of globalization and anarchy regarding global security concerns and global order in general, one can expect a dramatic shift to soft power in approaching unresolved sensitive issues that have plagued and petrified the whole system of international relations. But since there is friction and lack of constructive communication between great powers global disorder will continue to disperse divergences, conflicts, exclusions, cultural-ideological biases and extremism around the world. The world environment reveals itself uncertain with a bunch of challenges ahead that require the utilization of soft power values and its potential to resolve some of these sensitive issues in a durable time frame. Although globalization tends to shrink the role of hard power in general because of the growing interdependence relation among states, one can still observe some cases where states base their actions solely on hard power or are still attached to its means and strategies. Conversely, other states seem unwilling to share and exchange values or attracts other actors or states by argument or persuasion in order to achieve common goals. This paper aims to analyze the role of soft power, namely the power to persuade and attract through its “values dimension”, its effectiveness to complement hard power and cases where its role has been ignored.
Keywords: soft power, hard power, unresolved challenges, world order, public diplomacy